2023
DOI: 10.1186/s12888-023-04754-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of depressive symptoms and social support in the association of internet addiction with non-suicidal self-injury among adolescents: a cohort study in China

Abstract: Background Both internet addiction (IA) and non-suicidal self-injury (NSSI) are major public health concerns among adolescents, however, the association between IA and NSSI was not well understood. We aimed to investigate the association between IA and NSSI within a cohort study, and explore the mediated effect of depressive symptoms and the moderating effect of social support in the association. Methods A total of 1530 adolescents aged 11–14 years… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…A study analyzed the survey data of 11,813 adolescents in Shandong Province and found that long-term use of mobile phones was positively correlated with the risk of depressive symptoms [ 68 ]. In addition, a cross-sectional study based on SEM found that depressive symptoms mediated the association between IA and non-suicidal self-injury [ 69 ], which also supported our findings to some extent.…”
Section: Discussionsupporting
confidence: 90%
“…A study analyzed the survey data of 11,813 adolescents in Shandong Province and found that long-term use of mobile phones was positively correlated with the risk of depressive symptoms [ 68 ]. In addition, a cross-sectional study based on SEM found that depressive symptoms mediated the association between IA and non-suicidal self-injury [ 69 ], which also supported our findings to some extent.…”
Section: Discussionsupporting
confidence: 90%
“…We constructed a direct acyclic graph (DAG; eFigure in Supplement 1) to select potential confounders when examining the association between parental migration and aggression among their offspring. Specifically, we selected study province (Heilongjiang, Hubei, Anhui, Guangdong, and Yunnan), age (continuous), sex (male or female), child’s ethnicity (Han or others), single-parent family (yes or no), single-child family (yes or no), family income (<$150/mo, $150-$850/mo, or >$850/mo), educational level of the main caregiver (middle school or below, high school or technical school, college or above), parenting style (strict, pampered, neglect or frequently changing, or open-minded), social support (continuous), loneliness (continuous), psychological resilience (continuous), and emotional management ability (continuous) as the potential confounders. Information on measurements of these confounders can be found in eMethods in Supplement 1.…”
Section: Methodsmentioning
confidence: 99%
“…), decreased academic performance (reduced attention and memory), and anxiety and depression in some mental diseases [ 6 , 7 ]. And with time, non-suicidal self-injury and suicidal ideation of teenagers with Internet addiction showed an upward trend [ 8 , 9 ]. Therefore, teenagers’ IA is a concern in China and many other countries.…”
Section: Introductionmentioning
confidence: 99%